2019
DOI: 10.1038/s41593-019-0339-x
|View full text |Cite
|
Sign up to set email alerts
|

The DNA modification N6-methyl-2’-deoxyadenosine (m6dA) drives activity-induced gene expression and is required for fear extinction

Abstract: DNA modification is known to regulate experience-dependent gene expression. However, beyond cytosine methylation and its oxidated derivatives, very little is known about the functional importance of chemical modifications on other nucleobases in the brain. Here we report that in adult mice trained in fear extinction the DNA modification N6-methyl-2’-deoxyadenosine (m6dA) accumulates along promoters and coding sequences in activated prefrontal cortical neurons. The deposition of m6dA is associated with increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 60 publications
2
63
0
Order By: Relevance
“…Deciphering the exact pathway by which the knockdown of KMT9α leads to non-apoptotic cell death should be investigated in future studies. Recently, Li et al [35] have correlated N6AMT1 expression with m6dA marks in murine neurons that are associated with activity-induced gene expression. Notably, the experiments by Li et al were performed in post-mitotic neurons suggesting that the functions of KMT9 include but are not limited to regulating proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Deciphering the exact pathway by which the knockdown of KMT9α leads to non-apoptotic cell death should be investigated in future studies. Recently, Li et al [35] have correlated N6AMT1 expression with m6dA marks in murine neurons that are associated with activity-induced gene expression. Notably, the experiments by Li et al were performed in post-mitotic neurons suggesting that the functions of KMT9 include but are not limited to regulating proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…In this experiment, we used fluorescence-activated cell sorting (FACS) on neurons labeled with the neuronal nuclei marker (NeuN) and activity-regulated cytoskeleton-associated protein (Arc; see Figure 1b ). The NeuN marker allows for differentiation of non-neurons from neurons, and the Arc marker differentiates between recently activated neurons and quiescent neurons 18 . We found that fear extinction-trained mice exhibited significantly higher levels of Adar1 mRNA expression in activated neurons (high Arc) than in quiescent neurons (low in Arc) from the same animal ( Figure 1c ).…”
Section: Resultsmentioning
confidence: 99%
“…However, Adar1 binding to DNA was minimal during the formation of Z-DNA, suggesting that under these conditions Adar1 does not coordinate the formation of Z-DNA 33 . Instead, DNA methylation 20 24 , local salt changes 18 , or endogenous synthesis and release of polyamines 34 may contribute to the formation and stabilization of Z-DNA at these sites. Overall, it may only be through the ability of Z-DNA to modulate downstream events such as gene expression or RNA editing that its functional importance for cellular memory can be observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A host of previous work has demonstrated relationships between hippocampal-prefrontal function, BDNF, and fear behavior 15,16 , including work from our laboratory showing that mice with decreased production of activity-dependent BDNF have deficits in fear extinction that co-occur with impaired hippocampal-prefrontal oscillatory synchrony 31 . Transcription from promoter IV of the Bdnf gene in the dorsal hippocampus is correlated with fear memory consolidation 32 and epigenetic modification of promoter IV in the IL is linked with fear extinction 33,34 , findings that suggest that BDNF production from promoter IV may contribute to the mechanism underlying fear behavior 35 . Our lab recently demonstrated that synthetic excitation of cells in the ventral dentate gyrus expressing promoter IV-derived Bdnf transcripts increased freezing during context fear retrieval and concomitantly attenuated vHC-PrL oscillatory synchrony 36 .…”
Section: Activity-dependent Bdnf Signaling Alters Vhc-prl Function Dumentioning
confidence: 99%